CYTOGENETIC PROFILING IN PAEDIATRIC ACUTE LEUKAEMIA; A REPORT ON 746 NEWLY DIAGNOSED PAEDIATRIC CASES ANALYZING THE SPECTRUM OF RECURRING CHROMOSOMAL REARRANGEMENTS IN B CELL LYMPHOBLASTIC AND ACUTE MYELOID LEUKAEMIA - Meraj, Fatima; Jamal, Saba; Javed, Omer; Maqsood, Sidra; Mansoor, Neelum; Jabbar, Naeem (Journal of Ayub Medical College Abbottabad, 2023)
Background: Cytogenetics is evolving and different molecular mechanisms we know now have proved to be of diagnostic and prognostic significance in both acute lymphoid (ALL) and myeloid leukaemia (AML). This study aims to find out and compare the occurrence of different cytogenetics in paediatric acute leukaemia. Methods: This is a cross-sectional study of diagnosed B-ALL and AML patients presenting at The Indus Hospital. We studied FISH and karyotype in B-ALL and FISH in AML patients. FISH analysis shows a total of 69 (12.8%) of B ALL patients had cytogenetic abnormalities. BCR-ABL1 was positive in 5.1%, ETV6/RUNX1T1 in 8.6% and KMT2A in 2.3% individuals. Karyotype reveals hyper diploidy in 24.3%, Monosomy in 1.94%, and t (1:19) and t (17:19) were observed in 5.8 % and 0.24% cases respectively. FISH analysis in AML cases reveal positivity of t (8:21) in 26.4%, INV (16) in 6.1% while PML-RARA t(15:17) was done on morphological suspicion in 17 cases; all of which showed positivity; making 7.9% of the total AMLs. The study demonstrated a wide spectrum of heterogeneity in paediatric acute leukaemia. Conclusion: Hyperdiploidy was the most common cytogenetic abnormality. We report a lower incidence of t (12:21), compared to the world. We showed a higher prevalence of RUNX1/RUNX1T1 in young children. The prevalence of core binding factor AML was 32.5%.